Analisis Aktivitas Olahraga Panjat Tebing Kerud Kabupaten Sumedang - Rusnindar, Dera; Susilawati, Dewi; Fauzi, Rizal Ahmad (UNIB Press, 2025)
The rise of rock climbing sports in any circle regardless of age and gender, rock climbing sports are also classified as recreational sports as well as extreme sports of course with this certainly giving rise to several different views and assessments especially in Sumedang Regency which indeed only has a few cliffs. The new cliff is Kerud Cliff which is located in Jatihurip Village, Sumedang. This study aims to analyze rock climbing sports activities and see the potential for rock climbing tourism in Kerud Cliff, Sumedang Regency. By using a qualitative method approach and phenomenological design, this study focuses on the experiences, perceptions, and meanings given by the community, rock climbing enthusiasts who are often active in rock climbing sports that are developing in their area. The data collection method is through triangulation with participatory observation, in-depth interviews, and documentation with 6 informants consisting of 2 local residents, 2 Mapala and often rock climbing activities, and 2 general nature lovers.